Design of Battery Charging Time Based on Microcontroller - Indra Gunawan Yusuf Siregar (Brilliance: Research of Artificial Intelligence, 2022)
In this study, a tool is designed to compare the charging time of several batteries with charging using a solar tracker or not using a solar tracker to find out which battery is more efficient in its use. This research uses lead acid battery, lithium ion battery, and nickel-cadnium battery. From the results of this study, it is known that the lead acid battery has a charging time of 3 hours 30 minutes without using a solar tracker and 3 hours 15 minutes using a solar tracker with an efficiency of 7.14%, lithium ion batteries have a charging time of 3 hours 30 minutes without using a solar tracker and 3 hours using a solar tracker with an efficiency of 14.29%, while Nickle-Cadnium has a charging time of 4 hours 30 minutes without using a solar tracker and 4 hours 45 using a solar tracker with an efficiency of 11.11%. Then it was found that lithium ion batteries have the fastest charging time of the three batteries used.